Staphylococcus aureus and Escherichia coli dual‐species biofilms on nanohydroxyapatite loaded with CHX or ZnO nanoparticles. Issue 2 (31st October 2016) - Barros, Joana; Grenho, Liliana; Fontenente, Sílvia; Manuel, Cândida M.; Nunes, Olga C.; Melo, Luís F.; Monteiro, Fernando J.; Ferraz, Maria P.
Abstract: Implant‐associated infections are caused by surface‐adhering microorganisms persisting as biofilms, resistant to host defense and antimicrobial agents. Given the limited efficacy of traditional antibiotics, novel strategies may rely on the prevention of such infections through the design of new biomaterials. In this work, two antimicrobial agents applied to nanohydroxyapatite materials—namely, chlorhexidine digluconate (CHX) and zinc oxide (ZnO) nanoparticles—were compared concerning their ability to avoid single‐ or dual‐species biofilms of Staphylococcus aureus and Escherichia coli . The resulting biofilms were quantified by the enumeration of colony‐forming units and examined by confocal microscopy using both Live/Dead staining and bacterial‐specific fluorescent in situ hybridization. The sessile population arrangement was also observed by scanning electron microscopy. Both biomaterials showed to be effective in impairing bacterial adhesion and proliferation for either single‐ or dual‐species biofilms. Furthermore, a competitive interaction was observed for dual‐species biofilms wherein E. coli exhibited higher proliferative capacity than S. aureus, an inverse behavior from the one observed in single‐species biofilms. Therefore, either nanoHA‐CHX or nanoHA‐ZnO surfaces appear as promising alternatives to antibiotics for the prevention of devices‐related infections avoiding the critical risk of antibiotic‐resistant strains emergence. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 491–497, 2017.